Bridging self-confidence and learning flow: The role of psychological safety in high-fidelity simulation education - Lee, Soon-Hee; Yang, In-Suk (Nurse education today, 2025)
Self-confidence, psychological safety, and learning flow are key factors in high-fidelity simulation (HFS) education. While their individual effects on learning outcomes have been explored, the mediating role of psychological safety in the relationship between self-confidence and learning flow remains unclear. This study examines whether psychological safety mediates the relationship between self-confidence and learning flow in nursing students undergoing HFS education. A descriptive cross-sectional study was conducted with 149 nursing students from three South Korean universities. Data were collected via a web-based survey, and mediation analysis was performed using Baron and Kenny's method, with significance confirmed by the Sobel test. Self-confidence was positively correlated with psychological safety (r = 0.265, p = .001) and learning flow (r = 0.523, p < .001). Psychological safety also showed a significant positive correlation with learning flow (r = 0.395, p < .001). Mediation analysis confirmed that psychological safety partially mediated the effect of self-confidence on learning flow (Sobel test: Z = 1.977, p = .048). The effect size of the mediation effect was small but meaningful (κ2 = 0.026), indicating that psychological safety plays a significant role in enhancing the relationship between self-confidence and learning flow. Psychological safety enhances the positive impact of self-confidence on learning flow. Nursing educators should foster psychologically safe learning environments to maximize students' engagement and learning outcomes in HFS education. •Academic achievement, competencies, and HFS experience related to learning flow.•Confidence directly and indirectly affects flow through psychological safety.•Psychological safety partially mediates between confidence and flow.•Enhancing psychological safety can boost student engagement in HFS.